Relevance Weighting for Query Independent Evidence - Craswell, Nick; Robertson, Stephen; Zaragoza, Hugo; Taylor, Mike (Proceedings of ACM SIGIR 2005, 2005)
A query independent feature, relating perhaps to document content, linkage or usage, can be transformed into a static, per-document relevance weight for use in ranking. The challenge is to find a good function to transform feature values into relevance scores. This paper presents FLOE, a simple density analysis method for modelling the shape of the transformation required, based on training data and without assuming independence between feature and baseline. For a new query independent feature, it addresses the questions: is it required for ranking, what sort of transformation is appropriate and, after adding it, how successful was the chosen transformation? Based on this we apply sigmoid transformations to PageRank, indegree, URL Length and ClickDistance, tested in combination with a BM25 baseline.
://research.microsoft.com/users/nickcr/pubs/craswell_sigir05.pdf